Making the Newest Citizens: Achieving Universal Birth Registration in Contemporary Brazil. Issue 3 (4th March 2018) - Hunter, Wendy; Sugiyama, Natasha Borges
Abstract: Identity documentation is essential to secure the rights, benefits, and services that modern states provide. Historically, significant numbers of poor Brazilians lacked core documents, beginning with a birth certificate. In recent years the government has conducted a campaign to rectify this situation. We explore why the state left so many Brazilians without a birth certificate previously and why it became intent on registering all births, as reflected in recent efforts to facilitate the process. Key in this regard is the movement from a social policy orientation that excluded poor Brazilians in the informal sector to one aimed at including them.